EVALUASI SISTEM PENGENDALIAN INTERNAL PAJAK DAERAH DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN SURABAYA - Virdaleny, Virdaleny; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The background of government Internal Control System is the organization of activities at government agency,wich start from planning, implementing, monitoring, and up to the responsibility wich should be implemented in order,undercontrol, efficient, and effective. so the system wich can provide adequate convenience if the organization of activites at government agency can achieve its objectives efficient and effectively, the internal control of central and regional governmenton the basis of Government Regulation No. 60 of 2008 about the Government Internal Control System is required. This research is aimed to evaluate the Internal Control System on the local tax revenues to the Department of Revenue and Financial Management in Surabaya. The object of this research os the Department of Revenue and Financial Management (DPPK) in Surabaya. This research has been done by using qualitative descriptive method.The result of the research show that the internal control system of local tax revenue to the Department of Revenue and Financial Management (DPPK) in Surabaya is in accordance with Government Regulation No. 60 of 2008. The systems and procedures of local tax revenue in the Department of Revenue and Financial Management (DPPK) in Surabaya has been running well, it is suggested to give moreimprovement in developing the systems and procedures so that tax revenue can be run in accordance with the procedure.Keywords: internal control system, local taxes, local income